Detrital zircon geochronology in the Dora‐Maira and Zone Houillère: a record of sediment travel paths in the Carboniferous. (23rd May 2016) - Manzotti, Paola; Ballèvre, Michel; Poujol, Marc
Abstract: In the internal zone of the European Alps, late Carboniferous to Permian sediments have been detached from their basement (e.g. the Zone Houillère in the Briançonnais Zone). The Pinerolo Unit (Dora‐Maira Massif) is the deepest unit exposed in the stack of the Western Alps and is considered to be Carboniferous in age based on lithological considerations. Detrital zircon grains from the Pinerolo Unit and the Zone Houillère display similar age patterns, with the youngest and largest population being Carboniferous (340–330 Ma). The distribution of Carboniferous magmatism in the Alps and surrounding areas suggests that the detritus was transported from Maures‐Corsica and possibly from the Helvetic Zone into the Zone Houillère and the Pinerolo basin. Our results highlight the potential of detrital zircon geochronology for deciphering the sources of detrital material in meta‐sediments, even if they have been affected by metamorphic overprints.